In vivo analysis of the time and spatial activation pattern of microglia in the retina following laser-induced choroidal neovascularization. (October 2015) - Crespo-Garcia, Sergio; Reichhart, Nadine; Hernandez-Matas, Carlos; Zabulis, Xenophon; Kociok, Norbert; Brockmann, Claudia; Joussen, Antonia M.; Strauß, Olaf
Abstract: Microglia play a major role in retinal neovascularization and degeneration and are thus potential targets for therapeutic intervention. In vivo assessment of microglia behavior in disease models can provide important information to understand patho-mechanisms and develop therapeutic strategies. Although scanning laser ophthalmoscope (SLO) permits the monitoring of microglia in transgenic mice with microglia-specific GFP expression, there are fundamental limitations in reliable identification and quantification of activated cells. Therefore, we aimed to improve the SLO-based analysis of microglia using enhanced image processing with subsequent testing in laser-induced neovascularization (CNV). CNV was induced by argon laser in MacGreen mice. Microglia was visualized in vivo by SLO in the fundus auto-fluorescence (FAF) mode and verified ex vivo using retinal preparations. Three image processing algorithms based on different analysis of sequences of images were tested. The amount of recorded frames was limiting the effectiveness of the different algorithms. Best results from short recordings were obtained with a pixel averaging algorithm, further used to quantify spatial and temporal distribution of activated microglia in CNV. Morphologically, different microglia populations were detected in the inner and outer retinal layers. In CNV, the peak of microglia activation occurred in the inner layer at day 4 after laser, lacking an acute reaction. Besides, the spatial distribution of the activation changed by the time over the inner retina. No significant time and spatial changes were observed in the outer layer. An increase in laser power did not increase number of activated microglia. The SLO, in conjunction with enhanced image processing, is suitable for in vivo quantification of microglia activation. This surprisingly revealed that laser damage at the outer retina led to more reactive microglia in the inner retina, shedding light upon a new perspective to approach the immune response in the retina in vivo . Highlights: In vivo analysis of microglia activity using MacGreen mice. Identification of image processing algorithm applicable to conventional SLO. Identification and quantification of different microglia phenotypes in vivo . Higher activity of microglia in inner than outer retina after laser CNV. Increase laser power has no impact on level of microglia activation.